Severe non-atopic asthma: omalizumab can reduce severe asthma exacerbations. (4th May 2023) - Melscoet, Lise; Khayath, Naji; Migueres, Nicolas; Goltzene, Marc-André; Meyer, Nicolas; de Blay, Frédéric
Abstract: Introduction: Humanized monoclonal anti-IgE antibody (omalizumab) has demonstrated efficacy in severe atopic asthma. However, few studies have assessed its efficacy in non-atopic and even less in T2-low severe asthma. The objective was to determinate the omalizumab response according to atopic status. Methods: This retrospective, real-world study was performed in the Chest Diseases Department of Strasbourg University Hospital from January 1, 2006, to June 30, 2017. The response to omalizumab was assessed in 139 patients 4, 6, and 12 months after treatment and compared to data collected prior to omalizumab initiation. Results: Forty-four patients (31.7%) had severe non-atopic asthma and 95 (68.3%) had a severe atopic asthma. In the non-atopic group, omalizumab significantly reduced the severe exacerbation rate by 44% (95% CI 18-64%, p  < 0.05), 43% (CI 95% 20-60%, p  < 0.05), and 54% (CI 95% 36-67%, p  < 0.05), at 4, 6 and 12 months, respectively. A trend toward improvement in FEV1, asthma control and oral corticosteroid use was also observed. These results were not significantly different from those obtained in atopic asthmatics except a more effective oral corticosteroid sparing in atopic group ( p  < 0.05). Similar reduction of severe exacerbation rates were observed in T2-low asthma subgroup (non-atopic, non-eosinophilic). Conclusion: Omalizumab was effective in severe asthma, regardless of atopic status.